Juridical Analysis of the Position of PTUN in Resolving State Administrative Disputes - Ali, Safitri (Universitas Negeri Gorontalo, 2025)
This study analyzes the position of the State Administrative Court (PTUN) in resolving state administrative disputes by highlighting its role, function, and authority in protecting citizens' rights. Using a normative juridical method, this research examines the legal basis, principles, and practices of PTUN in upholding the rule of law, including case studies to understand its legal implementation in court. The findings indicate that PTUN plays a crucial role in overseeing government actions to ensure compliance with the law and good governance principles, despite challenges related to independence, effectiveness, and public accessibility. Therefore, enhancing judicial capacity, simplifying procedures, and strengthening institutional independence are necessary for PTUN to function optimally. In conclusion, PTUN serves as a vital judicial control mechanism within Indonesia’s legal system, and strengthening this institution is essential to fostering a more transparent, accountable, and just government.